2006
DOI: 10.1177/153100350601800123
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-  and Wound Healing

Abstract: Acute and chronic wounds are a source of significant morbidity for patients, and they demand a growing portion of health-care time and finances to be devoted to their care. Transforming growth factor-β (TGF-β) has surfaced from abundant research as a key signal in orchestrating wound repair. In beginning this review, we discuss the inflammatory, proliferative, and maturational phases of wound healing. We then focus on TGF-β by first discussing the pathway from its production to the target cell where Smad prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 6 publications
5
100
0
3
Order By: Relevance
“…Although Smad2 and Smad3 are reported to have a final common pathway, slight differences lead to different cellular effects. For instance, Smad3 directly interacts with DNA, whereas Smad2 requires other transcription factors to interact with DNA and affect gene expression (29). Apparently, in our research, we observed that Smad2, not Smad3, associates with myocardin to coactivate the SM22a promoter and also tremendously enhances SM22a expression in primary rat MSCs.…”
Section: Cooperation Of Myocardin and Smad2 In Inducing Differentiatisupporting
confidence: 53%
“…Although Smad2 and Smad3 are reported to have a final common pathway, slight differences lead to different cellular effects. For instance, Smad3 directly interacts with DNA, whereas Smad2 requires other transcription factors to interact with DNA and affect gene expression (29). Apparently, in our research, we observed that Smad2, not Smad3, associates with myocardin to coactivate the SM22a promoter and also tremendously enhances SM22a expression in primary rat MSCs.…”
Section: Cooperation Of Myocardin and Smad2 In Inducing Differentiatisupporting
confidence: 53%
“…TGF-b1 has a well-established regulatory role in wound healing influencing all stages of wound repair, mainly through induction of extracellular matrix deposition and down-regulation of matrix degradation (Son et al 2005, Faler et al 2006, Lamar et al 2008. In aged skin, topical application as well as systemic administration of TGF-b1 affects tissue repair rates (Beck et al 1993), accelerating wound closure and restoring normal healing (Pierce et al 1989, Son et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Transformacioni faktor rasta beta igra važnu ulogu u raznovrsnim ćelijskim funkcijama tokom svih faza zarastanja rane, uključujući produkciju ECM, ekspresiju proteaze, migraciju, hemotaksu, difrencijaciju i proliferaciju različitih tipova ćelija 18 . Sva tri izoformna oblika sintetizovana su i pronađena u trombocitima i makrofagima, a proizvode ih i osteoblasti inkorporirani u mineralizovani koštani matriks.…”
Section: Transformacioni Faktor Rasta Tgf-βunclassified
“…The transformation growth factor beta plays an important role in a variety of cellular functions during all phases of wound healing, including: ECM production, protease expression and migration, chemotaxis, differentiation and proliferation of different cell types 18 . All three isoforms are synthesized and found in platelets and macrophages, and also produced by osteoclasts incorporated in the mineralized bone matrix.…”
Section: Transformation Growth Factor Tgf-βmentioning
confidence: 99%